2019
DOI: 10.1002/jor.24333
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐Cruciate Retaining Total Knee Arthroplasty Does Not Restore Native Tibiofemoral Articular Contact Kinematics During Gait

Abstract: Bi-cruciate retaining (BCR) total knee arthroplasty (TKA) design preserves both anterior and posterior cruciate ligaments with the potential to restore normal posterior femoral rollback and joint kinematics. Abnormal knee kinematics and "paradoxical" anterior femoral translation in conventional TKA designs have been suggested as potential causes of patient dissatisfaction. However, there is a paucity of data on the in vivo kinematics and articular contact behavior of BCR-TKA. This study aimed to investigate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…In contrast, a recent series assessed in vivo kinematics with a modern BCR design and concluded that sagittal plane motion and tibiofemoral articular contact characteristics including pivoting patterns were not fully restored in BCR TKA patients during treadmill walking and step-up activities. 2,15,16 This series, however, did not determine whether BCR TKA provided better restoration of native kinematics compared to conventional TKA. Therefore, the utility of BCR TKA is still debated, that is, no studies have conclusively revealed whether there is truly a significant differences of knee biomechanics following BCR TKA compared to PCR TKA.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, a recent series assessed in vivo kinematics with a modern BCR design and concluded that sagittal plane motion and tibiofemoral articular contact characteristics including pivoting patterns were not fully restored in BCR TKA patients during treadmill walking and step-up activities. 2,15,16 This series, however, did not determine whether BCR TKA provided better restoration of native kinematics compared to conventional TKA. Therefore, the utility of BCR TKA is still debated, that is, no studies have conclusively revealed whether there is truly a significant differences of knee biomechanics following BCR TKA compared to PCR TKA.…”
Section: Introductionmentioning
confidence: 89%
“…The anteroposterior contact position of the medial compartment remained relatively constant on the center of the superior surface during weight-bearing knee flexion in patients with posterior cruciate-retaining (CR) TKA ( Suggs et al, 2009 ; Nicolet-Petersen et al, 2020 ). The medial articular contact position of bi-cruciate retaining (BCR) TKA translated posteriorly in the single stance phase of gait while moving anteriorly in the double stance phase ( Tsai et al, 2019 ), and the contact excursion in the medial side from the center to posterior during deep lunge and sit-to-stand motions was observed in 29 unilateral BCR TKA patients ( Arauz et al, 2019 ). Furthermore, the contact position moved around the center of the medial compartment in 15 healthy subjects during walking over the ground at self-selected speeds ( Gray et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The resection of the ACL in CR and PS TKA has been linked with patient dissatisfaction and in vivo kinematic asymmetries, 1,2,35 suggesting that the preservation of the ACL in BCR TKA has the potential to more naturally mimic healthy knee biomechanics and improve patient reported outcome measures. 5,6,36,37 However, there is a paucity of data available regarding the in vivo kinematics of the preserved cruciate ligaments in patients with contemporary BCR designs. Therefore, the aim of the present study was to investigate the in vivo effect of PTS on the stress within the preserved ACL during a weight bearing STS and single-leg deep lunge.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the sample size of this study is rather small and may be improved in future studies; however, there are many studies in the literature using similar or smaller sample sizes. 5,6,[48][49][50] Future studies may investigate the effect of PTS on knee ligament elongation patterns in patients with alternative TKA designs.…”
Section: Discussionmentioning
confidence: 99%